SISTEM PEMERINTAHAN SOFT-AUTORITHARIAN SINGAPURA DI TENGAH ARUS DEMOKRASI - Muhammad Imam Akbar Hairi (Jurnal Pemerintahan dan Politik, 2019)
The aim of this paper is to analyze about soft-autoritharian model of Singapore system politics. We show that even modern state like Singapore, using market economy system doesn’t effect to democratize in government politics. Although middle class growing so fast, but didn’t make them to push government adopting democracy system politics. In consequence more educated people in Singapore, didn’t lead to democratization in politics. We then check this because confucianism become the prior of the political culture in Singapore. Confucianism became the soul of government politics of Singapore. We also show that people of Singapore didn’t care about democracy in politics because of the government provides public facility and entertainment really outstanding.       Keyword : Democracy, Singapore, Soft-Autoritharian.